External Rotator Sparing with Posterior Acetabular Fracture Surgery: Does It Change Outcome? - Halil Ceylan; Ozgur Selek; Murat Inanir; Omer Yonga; Bahar Odabas Ozgur; Ahmet Y. Sarlak (Advances in Orthopedics)
This study analyses the results of the treatment with external rotator sparing approach in acetabular fractures to determine whether muscle sparing has a positive impact on functional outcome. 20 patients with a mean age of 45.9 years (range: 26–64) that had been treated for displaced acetabular fractures were included in this series. Short Musculoskeletal Function Assessment (SMFA) questionnaire and hip muscle strength measurement were done at the 24-month of follow-up period. The radiographic results at the final followup were excellent in 9 hips (45%), good in 6 hips (30%), fair in 4 hips (20%), and poor in one hip (5%) according to the criteria developed by Matta. The average SMFA score for all of the patients was 18.3 (range: 0–55.4). The mean dysfunctional and bother indexes were 17.2 and 20.6, respectively. The overall muscle strength deficit was 11.8%. The greatest loss of strength was in internal rotation. In patients with better postoperative reduction quality of acetabular fracture, peak torque, and maximum work of hip flexion, extension and also internal rotation maximum work deficit were significantly lower (P<0.05). Accurate initial reduction and longer postoperative muscle strengthening exercise programs seem critical to decrease postoperative hip muscle weakness after acetabular fractures.